(untitled) (Journal of Environmental Science and Natural Resources, 2013)
The study was conducted to evaluate the metal induced abnormalities in the liver of Schizothorax niger from Dal Lake seasonally for a period of two years. The varied seasonal metal concentrations for copper (66.77 ± 3.12 to 81.68 ± 3.51 ppm), zinc (73.81 ± 2.52 to 97.84 ± 4.62 ppm), iron (204.92 ± 5.21 to 296.51 ± 4.37 ppm) and manganese (01.13 ± 0.02 to 08.30 ± 1.00 ppm) were observed during the entire period of study. The highest concentration of metals was observed in the summer seasons and the lowest concentrations in the winter seasons during the study period. Further, histochemical analysis demonstrated enormous amount of metals (Cu, Fe and Zn) in the liver of Schizothorax niger in summer seasons during the entire study period. The subsequent effects of metals, demonstrated by wet digestion-based Atomic Absorption Method and histochemical methods showed histological changes on the liver of Schizothorax niger. The liver showed disruption of the hepatic cords with congestion and degenerative changes in hepatocytes that varied from mild in winter seasons to severe vascular degeneration in summer season. From the present study it may be concluded that the metals in the environment are polluting the water bodies and their subsequent deleterious effects harm the aquatic fauna particularly the sensitive native fish, Schizothorax niger which is one of the reasons for its decline from the fresh water resources of the Kashmir Valley. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14820 J. Environ. Sci. & Natural Resources, 5(2): 231-237 2012